Step-by-step ballet class : the official illustrated guide - Sibley, Antoinette (Contemporary Books, 1994)
Seven lessons follow a young dancer's development, from basic positions and postures to more advanced levels. Best Books for Children, 6th ed. This guide developed by the Royal Academy of Dancing in England gives material for various levels of development, including positions, movements, and advice on appearance. Seven lessons follow a young dancer's development, from basic positions and postures to more advanced levels. Bowker Authored Title code.